Opportunities for reducing coagulants usage in urban water management: The Oxley Creek Sewage Collection and Treatment System as an example. (15th November 2019) - Salehin, Sirajus; Kulandaivelu, Jagadeeshkumar; Rebosura, Mario; Khan, Wakib; Wong, Reece; Jiang, Guangming; Smith, Peter; McPhee, Paul; Howard, Chris; Sharma, Keshab; Keller, Jürg; Donose, Bogdan C.; et al.
Abstract: Iron and aluminium based coagulants are used in enormous amounts and play an essential role in urban water management globally. They are dosed at drinking water production facilities for the removal of natural organic matter. Iron salts are also dosed to sewers for corrosion and odour control, and at wastewater treatment plants (WWTPs) for phosphate removal from wastewater and hydrogen sulfide removal from biogas. A recent laboratory study revealed that iron dosed to sewers is available for phosphate and hydrogen sulfide removal in the downstream WWTP. This study demonstrates for the first time under real-life conditions the practical feasibility and effectiveness of the strategy through a year-long full-scale investigation. Over a period of 5 months, alum dosing at ∼190 kg Al/day to the bioreactor in a full-scale WWTP was stopped, while FeCl2 dosing at ∼160 kg Fe/day in the upstream network was commenced. Extensive sampling campaigns were conducted over the baseline, trial and recovery periods to investigate sulfide control in sewers and its flow-on effects on phosphate in WWTP effluent, H2 S in biogas, as well as on the WWTP effluent hypochlorite disinfection process. A plant-wide mass balance analysis showed that the Fe 2+ dosed upstream was effectively used for P removal in the activated sludge tanks, with an effluent phosphate concentration comparable to that in the baseline period (i.e. with alum dosing to the bioreactor). Simultaneously, hydrogen sulfide concentration in biogas decreased ∼43%, from 495 ± 10 to 283 ± 4 ppm. No effects on biological nitrogen removal and disinfection processes were observed. Both effluent phosphate and H2 S in biogas increased in the recovery period, when in-sewer dosing of FeCl2 was stopped. X-ray diffraction failed to reveal the presence of vivianite in the digested sludge, providing strong evidence that thermal hydrolysis prevented the formation of vivianite during anaerobic digestion. The latter limits the potential for selective recovery of Fe and P through magnetic separation. Overall, our study clearly demonstrates the multiple beneficial reuse of iron in a real urban wastewater system and urges water utilities to adopt an integrated approach to coagulant use in urban water management. Highlights: Long-term, field demonstration of 3-time uses of iron in an urban wastewater system. 3-uses include sulfide control in sewer and digester and P removal in bioreactor. Thermal hydrolysis destroyed vivianite in activated sludge. Thermal hydrolysis inhibited formation of vivianite during anaerobic digestion.